2004
DOI: 10.1167/iovs.04-0155
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography 3: Automatic Delineation of the Outer Neural Retinal Boundary and Its Influence on Retinal Thickness Measurements

Abstract: Incorrect delineation of the outer neural retina boundary is occurring with the automated retinal thickness measurement tool of the OCT3 software. At specific regions of the normal macula, retinal thicknesses were significantly underestimated due to such misalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
8

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 18 publications
4
82
0
8
Order By: Relevance
“…On the contrary, the algorithm of StratusOCT uses the anterior border of the innermost hyperreflective band as the border of the outer retina for calculating total RT. 21,25 Recent studies have shown that currently available FD-OCT devices are all giving significantly higher RT measurements than StratusOCT because of different assumptions considered for the detection of the outer retinal boundary, making the comparison of data obtained by different devices difficult (see Table 5). These differences also hinder the adequate evaluation of the performance of FD-OCT to detect the progression of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the algorithm of StratusOCT uses the anterior border of the innermost hyperreflective band as the border of the outer retina for calculating total RT. 21,25 Recent studies have shown that currently available FD-OCT devices are all giving significantly higher RT measurements than StratusOCT because of different assumptions considered for the detection of the outer retinal boundary, making the comparison of data obtained by different devices difficult (see Table 5). These differences also hinder the adequate evaluation of the performance of FD-OCT to detect the progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The segmentation software of the StratusOCT system uses the anterior border of the first or innermost hyperreflective band as the border of the outer retina for calculating total RT. 21 OCTRIMA calculates total RT as the distance between the vitreoretinal interface (ILM) and the anterior boundary of the second hyperreflective band corresponding to the OS/RPE junction. On the other hand, RT measurements of RTVue are taken between the ILM and the edge defined by the mean value of the maximum reflectance of the RPE in order to avoid detection errors at the RPE's outer border (personal information from the manufacturer, Optovue Inc., Fremont, California).…”
Section: Clinical Examinationsmentioning
confidence: 99%
“…The use of the Stratus OCT automated retinal thickness measurement tool has been thought to generate erroneous values because of the incorrect interpretation of the inner HRL as the outer neural retina boundary. 20,21 Manual caliper-assisted retinal thickness measurements, in which the outer HRL was interpreted as the outer boundary, at specific macular regions differed from those automatically generated by 9.9% from up to 38%. 20 The Spectralis OCT thickness algorithm calculates retinal thickness as the distance between the vitreoretinal interface and the Bruch's membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]16 On OCT imaging, the HRB is identified as a distinct band just above the highreflectance layer of the retinal pigment epitheliumchoriocapillaris complex, best detected in greyscale mode (Figure 2). 17 The HRB was analysed in the area corresponding to the central 3 mm grid of the ETDRS chart and classified into three groups: intact (group 1), disrupted (group 2), or absent (group 3), depending on …”
Section: Hyper-reflective Band (Hrb)mentioning
confidence: 99%